Sociotechnical Conditions for Introducing New Variety of Pineapple: Study of Area Development Program in Kediri District - Nugraheni, Indri (FIA UB, 2016)
In order to expand the pineapple market, the government introduced a new variety to Kediri District in 2011. The pineapple market was expanded successfully, but the supply of the new variety was not able to meet the demand, owing to the low production. This study describes the socio-technical aspects of the new variety introduction. The data were collected in two villages in Ngancar Sub-District, providing 86 samples of pineapple farmer households. From the result, for developing pineapple, new variety introduction which promises economic benefit needs to be conducted. Making sufficient seedling available in the early stage of new variety diffusion is substantial. In addition, the role of extension personnel and other parties, e.g. cooperatives, is important to supporting pineapple development.